PERAN KEPEMIMPINAN KEPALA SEKOLAH BERBASIS KEARIPAN LOKAL SASAK DALAM PENINGKATAN KEDISIPLINAN KERJA GURU MA NW RUMBUK - Ahmad Qolbi; Nurun Sholeh; Robyan Endru Bafadal (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2020)
The purpose of the study was to determine the role of the principal's leadership in improving the work discipline of MA NW Rumbuk teachers. The author presents a theoretical analysis that describes theories related to this research problem. This study uses a qualitative method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation. The data were analyzed using the Milles and Huberman analysis model. The study's results can provide an interpretation of the findings in the field so that it can be said that. The principal, as a manager, has a vital role in coordinating, mobilizing, and aligning all educational resources in the school—the principal is an educator where the thing taught by the mind is intelligence. As an administrator, the principal must be able to master his duties well. The principal is a motivator, a principal who is an essential part of the school.